PERSONAL DATA PROTECTION IN THE FIELD OF HEALTHCARE (CRIMINAL-LEGAL ASPECTS) - Ямненко, Тетяна Михайлівна; Літвінова, Ірина Феофанівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Objective: the research paper discloses the issue of personal data protection in the field of healthcare, legislative consolidation of such protection and liability in case of violation of the legislation. Research methodology: analysis, synthesis, generalization, deductive method, identification, logical approach, definition, description. Findings: the provisions of the current legislation on the personal data protection in the field of healthcare are determined and it is concluded that some of them need to be improved. The rules of the laws are generalized, according to which administrative, criminal and civil liability for violation of the legislation on personal data processing in the field of healthcare are established. Discussion: the existing mechanism for personal data protection in the field of healthcare and legislative novelties in connection with the implementation of the electronic healthcare system. The conducted research allows to state that personal data in the field of health care should be considered as a collection of information about the person (patient) that allows her to identify and information about her state of health, medical examinations, therapeutic measures, prognosis of the disease, as well as information, which are related to genetic data. Currently, the mechanism for protecting personal data is regulated by numerous legal acts, but there are provisions that need to be finalized and clarified. Reforms in the health system regarding the functioning of the electronic system generate the need for additional measures to protect the personal data that are being added to it. Administrative, criminal and civil liability has been established for violation of the legislation on the processing of personal data in the field of health care.